State and pressures of the marine and coastal Mediterranean environment. (Environmental assessment series, 1999)
The report, prepared by the European Environment Agency (EEA) and its European Topic Center on the Marine and Coastal Environment(AETC/MCE) in cooperation with the Mediterranean Action Plan(MAP), presents the overview of the Mediterranean marine and costal environment. The report makes an attempt to give a picture of the region and reflect important and characteristic features of the Mediterranean marine environment and the impacts of human activities, based on the best available information in 1997-98. It doesn't attempt to describe in detail the activities undertaken in the region by the various bodies but to present objectives and recommends actions to improve the quality and availability of information from the area.